PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP MINAT BELAJAR MATEMATIKA KELAS XI DI MAN - Miftahul Jannah; Isnaniah Isnaniah; Riki Effendi (ADIBA : JOURNAL OF EDUCATION, 2024)
The purpose of this research is to determine the use of wordwall learning media on interest in learning mathematics. The population in this study were class XI MIPA MAN 1 Pasaman students. The research method used is quantitative with a quasi-experimental research model in the form of a design with nonequivalent group. Research data was obtained through questionnaires, observation and documentation. Data processing analysis uses a simple linear regression test and Independent T-Test. The results of the research based on percentage calculations found that students' interest in learning mathematics using the wordwall learning media was _, while in the control class students who were not treated using the wordwall learning media showed lower interest in learning in the mathematics learning process, namely _. In the hypothesis test using the independent T-Test, the significance value (sig.2 tailed) was 0.000 < 0.05, so H0 was rejected and Ha was accepted. Based on the research results, it can be concluded that the wordwall learning media influences students' interest in learning mathematics at MAN 1 Pasaman.